The Effect of Repurchase Intent on The Millennial Generation Through E-Word Of Mouth (E-WOM) As An Intervention Variable on E-Satisfaction and E-Trust In Bukalapak E-Commerce - Gatot Wijayanto; Jushermi Jushermi; Aida Nursanti; Rovanita Rama; Yutiandry Rivai (Return : Study of Management, Economic and Bussines, 2023)
This study aims to evaluate the effect of repurchase intention on the millennial generation through e-word of mouth (e-WOM) as an intervention variable on e-satisfaction and e-trust in Bukalapak e-commerce. This study used quantitative approach and survey method using online questionnaire. The sample used was 185 respondents who were millennial generation users of Bukalapak. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of Partial Least Squares (PLS) software. The results showed that e-WOM has a significant positive influence on repurchase intent, e-satisfaction, and e-trust. In addition, repurchase intent also has a significant positive influence on e-satisfaction and e-trust. These findings suggest that e-WOM can be used as a strategy to increase repurchase intent, e-satisfaction, and e-trust in Bukalapak e-commerce. Therefore, Bukalapak needs to pay attention to and improve the quality of e-WOM that appears on their platform, as well as improve the quality of service and customer experience to strengthen customers' repurchase intent, e-satisfaction, and e-trust in the future.